2006
DOI: 10.2116/analsci.22.1135
|View full text |Cite
|
Sign up to set email alerts
|

Optically Specific Detection of D- and L-Lactic Acids by a Flow-Injection Dual Biosensor System with On-line Microdialysis Sampling

Abstract: A flow-injection dual biosensor system with microdialysis sampling is proposed for the simultaneous determination of Dlactic and L-lactic acids. The dialysate from the microdialysis tube is delivered to a sample loop of the six-way autoinjector and then automatically injected into the flow-injection line with a dual enzyme electrode arranged in perpendicular to the flow direction. The dual enzyme electrode is constructed by hybridizing a poly(1,2-diaminobenzene) film into two sensing parts which respond select… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
5
0

Year Published

2007
2007
2022
2022

Publication Types

Select...
4
2
2

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(5 citation statements)
references
References 19 publications
0
5
0
Order By: Relevance
“…The biosensor consisted of a triple enzyme electrode that selectively detected glucose, l -lactate, and pyruvate without significant cross-reactivity [79]. Similar flow injection-based online systems were described by the same group for l -glutamate, acetylcholine, and dopamine [80] and d -/ l -lactic acid [81]. …”
Section: Microdialysis Coupled To Biosensorsmentioning
confidence: 99%
“…The biosensor consisted of a triple enzyme electrode that selectively detected glucose, l -lactate, and pyruvate without significant cross-reactivity [79]. Similar flow injection-based online systems were described by the same group for l -glutamate, acetylcholine, and dopamine [80] and d -/ l -lactic acid [81]. …”
Section: Microdialysis Coupled To Biosensorsmentioning
confidence: 99%
“…Yao et al also reported an online system employing a triple -enzyme electrode for the detection of glucose, l -lactate, and pyruvate [69] . Similar fl ow injectionbased online systems were described by the same group for l -glutamate, acetylcholine, and dopamine [72] and d -/ l -lactic acid [73] .…”
Section: Non -Separation -Based Methods Of Analysismentioning
confidence: 93%
“…Liu et al [ 23 ] separated and measured L-lactic acid and D-lactic acid in kimchi and concluded that L-lactic acid was dominant in kimchi, and the content of L-lactic acid gradually increased during the fermentation process, while the content of D-lactic acid first increased and then decreased. Nanjo et al [ 24 ] developed an enzyme sensor system for the simultaneous determination of D-lactic acid and L-lactic acid in alcoholic beverages. The olfactory threshold and aroma characteristics of chiral flavor compounds may vary depending on the stereoisomers considered, so lactic acid isomers must be isolated to obtain an accurate assessment of their flavor characteristics.…”
Section: Introductionmentioning
confidence: 99%